EVALUATION OF THE CAPABILITY OF IMMOBILIZED CHLORELLA VULGARIS (BEIJERINCK, 1890) IN ALGINATE BEAD MATRIX AS A BIOADSORBENT FOR HEAVY METAL ZINC (Zn) - Putranto, Aldo Ferio; Hazmi, Nubli; Hariani, Nova; Arif, Muhammad Fauzi (Universitas Medan Area, 2025)
Bioremediation intends to use living organisms to remove or decompose pollutants, using their ability to metabolize or accumulate hazardous substances, thus reducing toxicity. This study aims to compare the removal efficiency of free suspended Chlorella vulgaris and immobilized Chlorella vulgaris. Monoculture isolates of Chlorella vulgaris were cultured in an aqueous medium with KW21 fertilizer for approximately 12 days until reaching the stationary phase. The biomass was harvested, dried, and separated. A ZnCl₂ solution was prepared with 2, 4, and 8 ppm working concentrations. The biosorption efficiency was calculated to evaluate the biosorption capacity. The results indicated that the removal efficiency of free suspended C. vulgaris was 14.73%, 6.76%, and 10.22% for the respective concentrations. Immobilized C. vulgaris exhibited significantly higher removal efficiencies of 73.79%, 77.87%, and 83.80%. This study shows that immobilizeed C. vulgaris have a higher removal efficiency value than free suspended C. vulgaris cells because they can withstand heavy metal toxicity better. This study implicates that the treatment of alginate beads increases the stability and effectiveness of biosorption, and makes this method a preferred approach for heavy metal bioremediation applications in aquatic environments.